Photometric, spectral phase and temperature effects on 4 Vesta and HED meteorites: Implications for the Dawn mission - Reddy, Vishnu; Sanchez, Juan A.; Nathues, Andreas; Moskovitz, Nicholas A.; Li, Jian-Yang; Cloutis, Edward A.; Archer, Ken; Tucker, Roy A.; Gaffey, Michael J.; Paul Mann, J.; Sierks, Holger; Schade, Ulrich (Icarus (New York, N.Y. 1962), 2012)
► We have derived photometric, spectral phase and temperature functions for Vesta. ► Spectral phase functions affect band parameters i.e. band depth and Band Area Ratio. ► Temperature affects the Band I and II centers of the pyroxene absorption band. ► These effects need to be corrected for before mineralogical characterization. Phase angle and temperature are two important parameters that affect the photometric and spectral behavior of planetary surfaces in telescopic and spacecraft data. We have derived photometric and spectral phase functions for the Asteroid 4 Vesta, the first target of the Dawn mission, using ground-based telescopes operating at visible and near-infrared wavelengths (0.4–2.5 μm). Photometric lightcurve observations of Vesta were conducted on 15 nights at a phase angle range of 3.8–25.7° using duplicates of the seven narrowband Dawn Framing Camera filters (0.4–1.0 μm). Rotationally resolved visible (0.4–0.7 μm) and near-IR spectral observations (0.7–2.5 μm) were obtained on four nights over a similar phase angle range. Our Vesta photometric observations suggest the phase slope is between 0.019 and 0.029 mag/deg. The G parameter ranges from 0.22 to 0.37 consistent with previous results (e.g., Lagerkvist, C.-I., Magnusson, P., Williams, I.P., Buontempo, M.E., Argyle, R.W., Morrison, L.V. [1992]. Astron. Astrophys. Suppl. Ser. 94, 43–71; Piironen, J., Magnusson, P., Lagerkvist, C.-I., Williams, I.P., Buontempo, M.E., Morrison, L.V. [1997]. Astron. Astrophys. Suppl. Ser. 121, 489–497; Hasegawa, S. et al. [2009]. Lunar Planet. Sci. 40. ID 1503) within the uncertainty. We found that in the phase angle range of 0° < α ⩽ 25° for every 10° increase in phase angle Vesta’s visible slope (0.5–0.7 μm) increases 20%, Band I and Band II depths increase 2.35% and 1.5% respectively, and the BAR value increase 0.30. Phase angle spectral measurements of the eucrite Moama in the lab show a decrease in Band I and Band II depths and BAR from the lowest phase angle 13° to 30°, followed by possible small increases up to 90°, and then a dramatic drop between 90° and 120° phase angle. Temperature-induced spectral effects shift the Band I and II centers of the pyroxene bands to longer wavelengths with increasing temperature. We have derived new correction equations using a temperature series (80–400 K) of HED meteorite spectra that will enable interpretation of telescopic and spacecraft spectral data using laboratory calibrations at room temperature (300 K).